2011
DOI: 10.1007/s00547-003-0949-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical revascularization on buerger's disease patients: A twelve-year experience

Abstract: Buerger's disease is an inflammatory disorder that involves the vessels of the extremities, affects young smokers and frequently leads to critical limb ischemia. The operative procedures are an important share of the complex treatment but the results from surgical revascularizations are still debatable. The analysis presented covers a 12 year experience with the surgical revascularizations on 81 thromboangiitis obliterans (TAO) patients, out of a group of 165. A total of 47 sympathectomies and 42 arterial reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies have shown satisfactory results after revascularization procedures with good long-term patency rates and ulcer healing. [12][13][14][15] Our overall patency rate was 64.8% and the limb salvage rate was 80.9% after revascularization. Endovascular treatment has shown promising results according to a few studies.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown satisfactory results after revascularization procedures with good long-term patency rates and ulcer healing. [12][13][14][15] Our overall patency rate was 64.8% and the limb salvage rate was 80.9% after revascularization. Endovascular treatment has shown promising results according to a few studies.…”
Section: Discussionmentioning
confidence: 72%